A study of the influence of orifice diameter on a turbulent jet ignition system through combustion visualization and performance characterization in a rapid compression machine. (25th April 2015) - Gentz, Gerald; Thelen, Bryce; Gholamisheeri, Masumeh; Litke, Paul; Brown, Adam; Hoke, John; Toulson, Elisa
Abstract: Turbulent Jet Ignition is a prechamber initiated combustion system that can replace the spark plug in a standard spark ignition engine. The nozzle orifice is critical in a turbulent jet ignition system as it determines the shape and structure of the jet which acts as a distributed ignition source. In this paper, the effect of nozzle diameter and number was studied by performing combustion visualization and characterization for combustion of a premixed propane/air mixture initiated by a turbulent jet ignition system in a Rapid Compression Machine. Color images of the jet ignition process and visualization of the emission of the chemiluminesence of OH ∗ and CH ∗ radicals were performed. Several nozzle configurations were tested which expanded on the limited experimental results that were available in the literature. The performance of the turbulent jet ignition system based on the nozzle orifice diameter was characterized by considering the 0–10% and 10–90% burn durations of the pressure rise due to combustion. In general it was found that for near stoichiometric air to fuel ratios, a nozzle that produced more spatially distributed jets would result in faster combustion progression. However, at leaner conditions a smaller diameter nozzle that produced a faster and more vigorous jet was required to initiate combustion. The Reynolds number of the discharging jet for the single orifice cases was calculated and it was found that increasing the nozzle diameter increased the Reynolds number, and thus the turbulence for λ  = 1. The Reynolds number was not found to be sensitive to orifice diameter at the leaner condition of λ  = 1.25. Further characterization of the jet development leads to the conclusion that the jet was considered to be in the intermediate flow field, where the transient jet does not have enough time to become fully developed before it reaches the combustion chamber wall. Highlights: The influence of orifice diameter on a pre-chamber turbulent jet ignition system was studied. High speed imaging of the turbulent jet ignition process was performed. Pressure data was collected to compare the combustion performance of different nozzles. Small nozzle orifice diameter was found to be advantageous to combustion initiation.